The study of amyloid beta (Aβ) induced ADF/cofilin rods in cultured neurons: implications in Alzheimer's disease and neurodegeneration - Maloney, Michael T., author; Bamburg, James R., advisor; Curthoys, Norm, committee member; Nyborg, Jenny, committee member; Partin, Kathy, committee member; Tobet, Stu, committee member (Colorado State University. Libraries, 2006)
Rods are intracellular proteinaceous aggregates composed mainly of actin saturated with ADF/cofilin that form in response to stress. Neurodegenerative stress mimicked in vitro with ATP depletion, glutamate excitotoxicity and peroxide all are potent mediators of rod formation. In neurons, rods form in linear arrays within neurites and disrupt distal neurite function. Rods can become large enough to completely occlude the neurite and thereby disrupt distal microtubules interfering with anterograde and retrograde transport. Treatment of both organotypic hippocampal slice cultures and dissociated neuronal cultures with as little as 10 nM of soluble amyloid beta peptides (Aβ1-42) induces rod formation. Aβ1-42 induces rods in half the responding population of dissociated neurons within 6 hours and a maximal response of less than 20% of neurons with rods occurring by 24 hours. Thus Aβ1-42 induced rods form rapidly in a sensitive sub-population of neurons. Transport defects are among the earliest abnormalities to occur in the brains of an AD mouse model (Tg-swAPPprp) and synaptic pruning associated with cognitive decline begins to occur before overt neuronal loss. In cultured neurons accumulation of vesicles containing the amyloid precursor protein (APP), β-amyloid cleavage enzyme, and presenilin 1 (a member of the γ-secretase complex) occur at rods. These trafficking defects may represent a site for increased amyloidogenic processing of APP into the Aβ peptides associated with Alzheimer's disease (AD) related senile plaques, extracellular deposits of aggregated Aβ peptide. In human AD brain nearly every senile plaque is associated with rod-like cofilin pathology. A feed foreword catalytic spiral is proposed wherein transient stress or Aβ induces rods leading to increased local Aβ production within stalled vesicles followed by increased extracellular Aβ, senile plaque deposition and further rod formation in the surrounding neuropil. Work included in this dissertation establishes a hippocampal slice culture system. Slice cultures will allow for continued investigations into the phenomenon of Aβ induced rod formation in an experimentally manipulatible system where neurons are kept in a more normal relationship with their surrounding cells. Such a system can be used to study the progression and pathology of Alzheimer's disease and other neurodegenerative amyloidopathies.
Keywords: neurology; molecular biology; neurosciences